THE APPLICATION OF ARCGIS IN THE GEOLOGICAL ANALYSIS AND ENVIRONMENTAL MANAGEMENT OF THE POTASSIUM DEPOSIT - Xoliyorova Xilola Komil qizi (Modern American Journals, 2025)
The present article explores the application of ArcGIS software in the geological modelling, resource assessment and environmental monitoring of the Tepakuton potassium deposit in Uzbekistan. The integration of diverse geospatial datasets, encompassing borehole data, structural geology, topography, and environmental baselines, has been demonstrated to enhance the understanding of complex salt-bearing formations.